Morphology of bony callus growth in healing of a sheep tibial osteotomy. Issue 1 (January 2021) - Wilson, Cameron J.; Epari, Devakara R.; Ernst, Manuela; Arens, Daniel; Zeiter, Stephan; Windolf, Markus
Highlights: The progression of periosteal callus formation was quantified from weekly radiographs of long bone healing in a sheep model. Under controlled fixation, bony callus had formed adjacent to the osteotomy site by two weeks, and grew outwards. Although contrary to a common view of healing patterns, this is consistent with a role for bony callus in reducing interfragmentary strain. Abstract: Long bone fractures typically heal via formation of an external callus, which helps stabilise the bone fragments. Callus composition and morphology influence the mechanical environment, which in turn regulates the progression of healing. Therefore characterising callus development over time is crucial in understanding this mechanobiological regulation. Although bony callus is often assumed to grow towards the fracture from either side, this is not consistent with observations from large animal studies and clinical cases. Therefore, we sought to quantify the morphology of bony callus over time in a large animal model. Sheep tibiae were x-rayed weekly over eight weeks following an osteotomy ( n =5), with fixation allowing up to 10% axial displacement under normal weight-bearing. After scaling radiographs by known landmarks and normalising greyscales, bony callus boundaries were defined by manual segmentation. The lateral callus area and coordinates of its centroid were calculated from each image. The external callus initially formed adjacent to the osteotomy site. Over the first four weeks, callus growth from its outer surfaces was characterised by its centre of area moving outwards and away from the osteotomy, on both proximal and distal fragments. Subsequent weeks showed consolidation and resorption from the outer surface of the callus. Our approach allowed bony callus development to be tracked in individuals throughout healing. Contrary to the view that periosteal bone formation originates distant from the fracture, our data showed bony callus adjacent to the defect from early stages, followed by approximately concentric growth. This discrepancy highlights the need for data specific to experimental conditions, and particularly early stages of healing, for evaluating theoretical models of mechanical regulation.